Takwīn al-Muṣṭalaḥāt al-ʿArabiyyah al-Ḥadīthah fī Majāl aṭ-Ṭibb: Dirāsah Taḥlīliyyah fī al-Muʿjam al-Mawrid al-Muzdawaj wa al-Muʿjam aṭ-Ṭibbī Nūriyah - Aufa Alfian Musthofa (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2017)
The development of language is closely related to the development of time. As language evolves, new terminology emerges to replace older terms or to designate newly invented concepts that require linguistic representation. The development of terminology is particularly evident in the fields of science, technology, and the arts, with the most rapid growth occurring in medical science. This development is largely attributed to the extensive research and innovations of Western scholars in medicine. For example, the English medical term AIDS has been borrowed into Arabic through transliteration as إيدز (Īdz). Other medical terms have been formed through different processes, such as Hypervitaminosis, Laser, Cornea, Allergic, Targeting, and many others. Understanding the formation of these terms requires appropriate linguistic approaches to facilitate the comprehension of modern medical terminology in Arabic. Researchers therefore need systematic methods for developing Arabic medical terminology in the future. This study presents several methods used in the formation of modern Arabic medical terminology, including translation, borrowing, blending (naḥt), and hybrid borrowing. In the translation method, the study identifies eighty new morphological patterns used in modern Arabic medical terminology, including biliteral, hexaliteral, heptaliteral, octoliteral, and nonaliteral patterns. Regarding the borrowing method, the study finds the adoption of letter-by-letter transliteration as well as the borrowing of English affixes into Arabic.